An investigation into the funding gap on operations: a case study of African Sun limited. - Mapa, Norman T. (Midlands State University, 2017)
This research was undertaken to investigate the impact of funding shortages on the operations using the case study of African Sun Ltd. The background to the study, research problems and objectives were identified which included the identification of possible sources of funding, determining the existence of a funding policy at African Sun Ltd and determining the best funding practices possible. Funding related literature was reviewed with major authors Dzirutwe (2015) asserting that the existence of stringent regulatory settings and tight policies in an economy, ministry or sector discourage the flow of funds especially through Foreign Direct Investments (FDIs)and Garg (2014) arguing that it is a firm’s debt level and its creditworthiness that attract or discourage investors. The main sources of data used in the research were primary and secondary sources of data. One research design method was used which is the descriptive research design method. Questionnaires were administered to middle management and the finance department staff. Major findings showed that majority of the employees are not fully aware of the funding policy of African Sun and respondents asserted that the prevailing economic conditions have also been the major reason why the funding gap has widened overtime.